(untitled) (Journal Of Educational and Psychological Researches, 2015)
The present study aimed to: 1 - To identify the leisure time activities among young people university . 2 - To identify statistically significant differences in leisure time activities among the students of the university depending on the variable. Gender (male , female ) and the study sample consisted of (152) students from the University of Baghdad College of Education, Ibn al-Haytham was randomly selected by (67) of the males and(85) females and dish them a measure of leisure-time activities that the researcher has ever built and achieved sincerity and firmness , sell statistical treatment showed results that the nature of the activities, leisure time importance in the exercise on according to type males or females in activity of religious duties results did not show any differences between males and females in the exercise of this activity while the study revealed that there are differences statistically significant between males and females in other leisure-time activities